Faces, Close-ups and Choreography: A Deleuzian Critique of So You Think You Can Dance - Dodds, Sherril; Hooper, Colleen (The International Journal of Screendance, 2014)
In everyday life the face occupies a central position within human expression and social interaction: its features are perceived to present a unique identity, and we breathe, consume and communicate through our faces. In this article, we explore two ideas as a means to examine the “screendance face.” First we introduce the notion of “facial choreography” to reflect on how the screen apparatus produces representations of dancing faces informed by aesthetic and social values. Secondly, we develop the concept of a “choreographic interface,” which we conceive as an intertextual site of meaning whereby a dancing face both references and enters into a dynamic exchange with other faces. While these two concepts could be applied to any screendance face, to elucidate these ideas in motion, we turn to a specific screendance case study: an audition clip from So You Think You Can Dance, which features Brian Henry, a 22-year old African American man from Brooklyn, New York, who specializes in krumping.